VIRUS-LIKE IMMUNOSTIMULATORY COMPLEXES BASED ON PLANT SAPONINS: PREPARATION, QUALITY CONTROL, ADJUVANT PROPERTIES - V. A., Evseenko; A. S., Gudymo; N. V., Danilchenko; K. I., Ivanova; A. V., Zaykovskaya; S. E., Olkin; O. S., Taranov; A. B., Ryzhikov (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
A promising approach to immunization is the use of saponin-based virus immunostimulatory complexes (ISCOM) and the creation of antigen complexes (ISCOM-antigen) based on them. Objective: production and study of virus-like immunostimulatory complexes based on Quillaja saponaria saponins. Materials and methods: using the tangential filtration method, the preparations of ISCOM adjuvant “Matrix-V”, were obtained. Electron microscopic study of the preparations confirmed expected object ultrastructure. The content of saponins, residual detergent in the preparation controlled by HPLC method. Immunization of guinea pigs, Balb/c mice with preparations of ISCOM-antigen (influenza virus A, B; Covid-19) performed intramuscularly. Blood serum samples of immunized animals examined in hemagglutination inhibition reaction, neutralization assay. Results: ISCOM containing Quillaja saponaria saponins were successfully qualified. Concentrations of saponins and residual detergent in the obtained preparations determined and were 47.9 mg/ml and 0.63 mg/ml respectively. As a result of a double intramuscular immunization of mice with 50 ng of hemagglutinin of each subtype, GMT in HI in serum was 1:735 - H1N1pdm09; 1:320 - H3N2; 1:91 - B(Yamagata); 1:60 - B(Victoria). No immune response to the vaccine in the same concentration without ISCOM was detected in HI. When immunized with Covid-19 antigens, virus neutralization titer was 1:20, with the Covid-19-ISCOM-adjuvant complex 1:1114 - 1:1436. The presented results indicate the promising use of ISCOM-based preparations in the development of vaccines.